Artificial Arm - Mohammad, Bahir; Salah, Ashwas (My University, 2017)
This project is talking about an artificial arm which is controlled by a human arm. The artificial arm contains motors and a set of cables connecting these motors altogether among all the five fingers. There are 5 flex sensors above the gloves of the human arm. On the artificial arm sideservo motor is attached with three cables; the +5 volts cable, the ground cable and the PWM(square wave signals). The angle of the servo is controlled by the PWM waves, and the range of change in the angle varies from 0-180. The movement of the artificial arm(the angle) depends on the flexion of the human arm(Flex sensor). Flex sensor is simply a changing resistance, and its resistance will change depending on the flexion of the human arm. When i move my arm, then the resistance angle will change. The voltage will go to the controller, and at the final stage; the controller will translate it to a PWM value and sends it to the servo